THE ENTREPRENEURIAL INTENTIONS OF URBAN YOUTH IN CHINA: A CONCEPTUAL ENTREPRENEURSHIP EDUCATION MEDIATION FRAMEWORK - Zhou , Chunmei; Bahari, Norzalizah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Urban entrepreneurship in China has been a key driver of economic transformation, social innovation, and job sustainability, particularly among youth people. However, despite the existence of various pro-entrepreneurship policies and a thriving innovation ecosystem, the actual rate of intention and engagement of urban youth in entrepreneurial activities is still modest. This paper conceptually reviews the factors of entrepreneurial intentions, focusing on the role of entrepreneurship education as a mediator within the framework Theory of Planned Behavior (TPB) and Resource-Based View (RBV). This paper aimed to review literature on personal attitudes, subjective norms, and perceived behavioral control in shaping entrepreneurial intentions, as well as how education influence these psychological dynamics. Literature review shows that personal attitudes, subjective norms, and perceived control of behavior are the main drivers of entrepreneurial intentions, but their effectiveness depends on the role of entrepreneurship education. This paper proposed a conceptual of TPB and RBV to elucidate the relationship between the dimensions of psychology and education in fostering entrepreneurship intentions of urban youth in China. This review offers theoretical contributions to the field of entrepreneurial intent studies and practical recommendations for policy makers, educators, and youth incubators.